2018
DOI: 10.1002/tcr.201800132
|View full text |Cite
|
Sign up to set email alerts
|

Practical and Scalable Organic Reactions with Flow Microwave Apparatus

Abstract: Microwave irradiation has been used for accelerating organic reactions as a heating method and has been proven to be useful in laboratory scale organic synthesis. The major drawback of microwave chemistry is the difficulty in scaling up, mainly because of the low penetration depth of microwaves. The combination of microwave chemistry and flow chemistry is considered to overcome the problem in scaling up of microwave-assisted organic reactions, and some flow microwave systems have been developed in both academi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 141 publications
0
9
0
Order By: Relevance
“…Principally, methodology based around microwave irradiation is not universally accessible -focussed microwave facilities for synthetic chemistry remain specialist and expensive -and scale-up of microwave processes is non-trivial due to the limited penetration depth of microwave irradiation, often requiring flow or multimode apparatus. [22][23][24] Further limitations include the narrow scope of the process, its harsh conditions (150 °C, 200 W, sealed tube), non-ideal stoichiometry and dependence on silica gel chromatography for product purification. Furthermore, as a telescoped process employing a different solvent for each step, the necessity to evaporate water (the solvent for alkylation) at the midpoint of the sequence is inconvenient and onerous.…”
Section: Introductionmentioning
confidence: 99%
“…Principally, methodology based around microwave irradiation is not universally accessible -focussed microwave facilities for synthetic chemistry remain specialist and expensive -and scale-up of microwave processes is non-trivial due to the limited penetration depth of microwave irradiation, often requiring flow or multimode apparatus. [22][23][24] Further limitations include the narrow scope of the process, its harsh conditions (150 °C, 200 W, sealed tube), non-ideal stoichiometry and dependence on silica gel chromatography for product purification. Furthermore, as a telescoped process employing a different solvent for each step, the necessity to evaporate water (the solvent for alkylation) at the midpoint of the sequence is inconvenient and onerous.…”
Section: Introductionmentioning
confidence: 99%
“…Because this field of research has been previously reviewed and a number of publications have reported the advances in MW-assisted organic synthesis (MAOS) in batch and in continuous flow mode, this Perspective has focused on recent studies with an emphasis on the advantages and limitations of MW heating. In this regard, synthetic protocols aimed at scaling up of the process and the comparison between different approaches directed to large-scale synthesis have been selected to provide a comprehensive picture of the state of the art.…”
mentioning
confidence: 99%
“…It is important to take into account that this type of synthesis the main obstacle is the difficulty in scaling up because of the low penetration depth of microwaves [ 75 ]. To overcome this, with the passing of the years, there has been a proposal based on the combination of microwave chemistry and flow chemistry.…”
Section: New Formulation Methodologiesmentioning
confidence: 99%